Epidemiology of sickle cell disease hospital admissions in Brazil - Loureiro, Monique Morgado (2005)
OBJECTIVE: Sickle cell disease is a hereditary disease, which affects mainly the black population. The aim of the present study was to analyze hospital admissions due to acute events resulting from sickle cell disease, at the epidemiological and clinical levels. METHODS: The study population included 9,349 patients with sickle cell disease admitted to hospitals in Bahia, Rio de Janeiro, and Sao Paulo, between 2000 and 2002. The national hospital database of the Brazilian Healthcare System was used. Response variables were death and mean duration of hospital admission. Covariables included sex, age, type of admission, and hospital legal status. Proportions were compared using Chi-square or Fischer tests; for continuous variables, the Mann-Whitney or Kruskall-Wallis tests were used. RESULTS: Median age ranged between 11.0 and 12.0 years, and 70% of admissions were of patients below age 20 years. Length of stay varied with age and type of admission. Emergency rooms were the most frequent form of admission (65.6 to 90.8%). Mortality was higher among adults. Median age of death was low (26.5 to 31.5 years). CONCLUSIONS: Our results confirm the high morbidity among youngsters and show a predominance of death among young adults.